NOMINAL GENDER AND NUMBER IN THE DEVELOPMENT OF THE TIMORESE VARIETY OF PORTUGUESE - Santos, Isabel A. (2019)
This study contributes to the description of East-Timorese Portuguese (ETP), focusing on the variable patterns of nominal agreement in number and gender operating in this variety. The relevance of the research hinges on the fact that ETP is an understudied non-native variety (NNV) of Portuguese. Given its emergent state, the study of this particular variety can furthermore shed light on the historical process that led to the formation of other NNV. NNV are a product of the non-native acquisition of a language that, in a given territory, takes on official status, this is to say, is a second language (SL). Comparing production data by NNV speakers and by foreign language (FL) learners can elucidate both common and specific patterns of behavior. In this study, texts written by ETP speakers and by PFL learners were compared. Results revealed similar trends in both samples, but also a greater preference of ETP speakers for not complying to full nominal agreement. In general, data suggest that variable patterns of nominal agreement are likely to emerge as a defining property of ETP, as is currently the case in other NNV of Portuguese, thus diverging from European Portuguese (EP).